ОБЕСЦЕНЕНИЕ ОСНОВНЫХ СРЕДСТВ - Амангалиева, А С (Journal of Economic Research & Business Administration, 2015)
This article describes how to depreciate fixed assets in accordance with IFRS, as well as testing for impairment of fixed assets. There is described the aim of testing.